A New Perspective on Children's Communicative Perspective Taking: When and How Do Children Use Perspective Inferences to Inform Their Comprehension of Spoken Language?. (26th August 2015) - San Juan, Valerie; Khu, Melanie; Graham, Susan A.
Abstract: Successful communication often requires a listener to reason about a speaker's perspective to make inferences about communicative intent. Although children can use perspective reasoning to influence their interpretation of spoken utterances, when and how children integrate perspective reasoning with language comprehension remain unclear. These questions are central to theoretical debates in language processing and have led to competing accounts of communicative perspective taking: early versus late integration. In this article, we examine how developmental evidence addresses the predictions of each account. Specifically, we review evidence to determine whether children can rapidly integrate perspective inferences when processing spoken language while central abilities (i.e., executive function and theory of mind) are still emerging.